KEPATUHAN IBU MEMBERI ASUPAN GIZI SESUAI INSTRUKSI PETUGAS DAN STATUS GIZI BALITA GIZI BURUK Di THERAPEUTIC FEEDING CENTRE KABUPATEN GORONTALO - OLII, NANCY (JURNAL HEALTH AND SPORT, 2012)
To determine the proportion of mothers compliance in giving nutrition according to the officer's instructions and nutritional status of malnutrition children in TFC of Gorontalo District. This study used the design of Case Control Study, with quantitative and qualitative approaches. A sample size was 120 people consisting of 60 people on the cases and 60 people on the control group. The sampling technique used a simple random sampling. The analysis of the data used the univariable analysis, bivariable using chi-square and multivariable analysis using logistic regression. The proportion of mothers who did not comply with the instruction to give nutrition to their child was 2.44 times greater in the group of under-nutrition than the normal nutrition group. Mothers Compliance had a significant relationship with under-five nutritional status (OR = 2.44, 95% CI = 1.09 to 5.48). Level of maternal education and number of children had a significant relationship with under-five nutritional status (OR = 3.85, 95% CI = 1.30 to 12.8; OR = 2.82, 95% CI = 1.25 to 6.380). The proportion of mothers who did not comply with the instruction to give nutrition to their child was greater in the under-nutrition group than the normal nutrition group.